Towards Optimizing Acetic Acid Utilization In Saccharomyces cerevisiae Through gRNA-Landing Pads - Berg, Erik (My University, 2024)
Lignocellulosic biomass, residual biomass from the agricultural and forestry industries, is the most abundant organic substance on the planet. For efficient utilization by Saccharomyces cerevisiae, the biomass must undergo a pretreatment process that typically generates strong inhibitors, with acetate being the most prominent. This project served as a proof of concept and explored optimization of acetate utilization in Saccharomyces cerevisiae using a gRNA-landing pad strategy. This was done through a wide range of molecular biology methods such as the transformation of Escherichia coli and the Saccharomyces cerevisiae strain LX6, restriction cloning, cloning using the MoClo system, as well as in-silico design of plasmids and primers. A gRNA-landing pad was successfully assembled in-vitro, using in-silico custom-made MoClo parts, and transformed into Escherichia coli. Transformation of the gRNA-landing pad into LX6 presented a challenge, that as of yet is not overcome. Despite the challenges in transforming the yeast, the creation of an easy-to-assemble gRNA-landing pad could enable a fast and reliable method for future research involving gRNA-landing pads Saccharomyces cerevisiae.